Stable isotope and ancient DNA analysis of dog remains from Cathlapotle (45CL1), a contact-era site on the Lower Columbia River. (May 2015) - Ames, Kenneth M.; Richards, Michael P.; Speller, Camilla F.; Yang, Dongya Y.; Lyman, R. Lee; Butler, Virginia L.
Abstract: This study reports ancient DNA (aDNA) and stable isotope analyses of eight dog skeletal elements from the Cathlapotle site on the Lower Columbia River of the western United States. The aDNA analysis confirmed the elements as dogs ( Canis lupus familiaris ). Two haplotypes were found, both of which group within dog Clade A, and have patchy distributions to the north in British Columbia and as far south as Teotihuacan (Mexico). The isotopic analysis showed that the dogs' dietary protein was derived almost exclusively from marine sources. Lower Columbia River ethnohistoric accounts and Cathlapotle zooarchaeological records indicate that while marine fish were dietary keystones, the local diet was more diverse, and included terrestrial organisms and freshwater fishes. This apparent discrepancy raises the possibility the dogs were selectively fed. Thus their diet may not be a close proxy for human diet in this context. Highlights: aDNA and δ 13 C and δ 15 N values from dogs from a village site on the Lower Columba River were analyzed. Two haplotypes present among the dogs were patchily present across North America. Isotopic values indicate a marina village site on e diet despite of a mixed marine/terrestrial diet. The dogs were probably being fed eulachon, a smelt.